Impact of Short First Medical Contact to Device Time on Final TIMI Blush Grade in Primary PCI - Nasrullah, Aftab Ahmed Solangi, Zahirullah, Amir Jamil, Khurshid Ali, Imran Abid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Greater first medical contact to device time has been observed to adversely effects the outcome of primary PCI. European Society of Cardiology (ESC) recommends a maximum of 90 min delay in FMC to device time. However, the effect of the FMC to the device time on the myocardial reperfusion (TIMI blush grade) is not assessed yet. Objective: To investigate the effect of the FMC to the device time on the TIMI blush grade of the STEMI patients who underwent primary PCI. Methodology: It was a prospective study consisting of 445 STEMI patients of Punjab Institute of Cardiology, Lahore, fulfilling the entry criteria in this study in the time period from January 2020 up to January 2022. The patients were divided into two study groups: those with FMC-D interval of < 90 min or short group and those with FMC-D interval of ≥ 90 min or the long group. TIMI blush grade was taken as the primary clinical endpoint whereas MACE at the 30 day follow up were taken as the secondary endpoints. Comparison of the clinical and peri-procedural outcomes was done among the two groups by SPSS. Results: The mean FMC-D time was 77.3 ± 32.1 minutes in short FMC-D time group and 117.1 ± 12.5 minutes in long FMC-D time group (p < 0.01). At the duration of 30 days, individuals in the long group showed significantly higher rates of MACE (14.2% vs 3.9%, p = 0.0002). Higher cardiac death rate was the driving force behind the noted difference (7.1% vs 1.2%, p = 0.002). Conclusion: First medical contact to device time does not significantly impact the final TIMI blush grade in patients underwent PCI. Patients in whom the delay of treatment is < 90 minutes have significantly lower rates of MACE at the 30 days duration. Keywords: First medical contact, TIMI blush grade, PCI, STEMI, FMC-D time.